Unusual aetiology of respiratory compromise in a patient with AIDS. Issue 3 (23rd March 2021) - Maaliki, Naji; Ali, Aleem Azal; Isache, Carmen Liliana; Aung, Win
Abstract : A 36-year-old African American man with no medical history presented with a recent history of cough and dyspnoea. Initial chest imaging revealed diffuse bilateral lung infiltrates. A subsequent HIV test resulted positive, and he was presumptively diagnosed with AIDS, later confirmed by a CD4 of 88 cells/mm 3 . Empiric therapy with trimethoprim–sulfamethoxazole was initiated for presumed Pneumocystis jirovecii pneumonia. The patient's clinical status deteriorated despite treatment. Further workup with chest CT, bronchoscopy and skin biopsy led to a diagnosis of Kaposi sarcoma with pulmonary involvement. Highly active antiretroviral therapy therapy was initiated, along with plans to start chemotherapy. However, the patient's clinical status rapidly declined, leading to respiratory failure and eventual death. This case underlines the importance of maintaining a broad differential in immunocompromised patients presenting with respiratory symptoms.